Heat-killed Bacillus subtilis concerning broilers’ performance, cecal architecture and microbiota - Yan Cui; Yan Cui; Weishuang Meng; Feng He; Feng He; Zeliang Chen; Zeliang Chen; Hongliang Liu; Desheng Li; Desheng Li; Desheng Li (Frontiers in Microbiology)
BackgroundAt present, Bacillus subtilis has been reported as a probiotic to be used as a feed additive to improve the production performance of broilers. However, the relevant reports on its derived postbiotics are still limited.MethodsIn this study, a total of 480 day-old Arbor acre broiler chicks with an initial body weight of 52.8 ± 1.4 g were used in this study to investigate the effects of dietary supplementation of graded levels of heat-killed B. subtilis on growth performance, cecal morphology, and cecal bacteria and fungus composition. Birds were assigned into four groups with six replicates of 20 birds each. The experiment was designed to last for 42 days. B. subtilis was supplemented with 0.000, 0.015, 0.030, or 0.045% heat-killed Bacillus subtilis (HKB).ResultsOur data indicate that body weight gain, gain to feed ratio, cecal villus height, and cecal villus to crypt ratio dose-dependently improved, while cecal crypt depth dose-dependently reduced, by HKB supplementation. Additionally, dietary supplementation of graded levels of HKB dose-dependently reduced cecal bacteria Chao1 index. Cecal bacteria identified by 16S rRNA and cecal fungus identified by ITS revealed that the supplementation of HKB regulate the composition of bacteria and fungus in cecum.ConclusionTherefore, dietary supplementation of HKB is an effective measure to improve cecal morphology by regulating cecal bacteria and fungus composition, and therefore improved growth performance.